Efficacy and safety of hydrogen peroxide topical solution in treating actinic keratosis: A randomized controlled trial. Issue 5 (19th August 2021) - Sadeghinia, Ali; Dastmalchi, Delara Amir; Kianfar, Nika; Dasdar, Shayan; Mahmoudi, Hamidreza; Dabiran, Soheila; Lajevardi, Vahideh; Daneshpazhooh, Maryam
Abstract: Actinic keratosis (AK) is a precancerous skin lesion associated with the development of squamous cell carcinoma. Approved topical treatments for AK are unmet needs. To evaluate the safety and efficacy of hydrogen peroxide topical solution 35% (H2 O2 ) with cryosurgery for the treatment of AKs. Eligible subjects were randomly assigned to receive H2 O2 and cryosurgery on each side of their scalp/face. Patients were assessed at baseline and after 3 months of follow‐up. Efficacy was evaluated based on the Actinic Keratosis Area and Severity Index (AKASI) and dermoscopic assessments. Fifteen patients with 98 lesions completed the study. At the follow‐up visit, the mean improvement of AKASI from baseline was 1.7 ± 0.9 for H2 O2 and 1.7 ± 0.8 for cryosurgery ( p < 0.001, both). Both treatments significantly improved dermoscopic features of yellow scale, white scale, linear‐wavy vessels, pigmented dots, and rosette at the end of the 3‐month follow‐up. Complete dermoscopic response occurred in 57.7% and 73.9% of lesions treated with H2 O2 and cryosurgery, respectively ( p > 0.05). Regarding safety, hypopigmentation occurred more frequently in the cryosurgery group (28.3% vs. 9.6%; p = 0.017). Moreover, patients endured more pain with cryosurgery application than H2 O2 ( p < 0.001). The effect of H2 O2 solution was comparable to cryosurgery. This treatment was well tolerated and had a favorable safety in patients with AKs.